Preparation method and application of thick film with gradient built-in electric field

By building a thick film with a gradient built-in electric field in an all-inorganic perovskite solar cell, the problems of insufficient thickness of the perovskite film and weak driving force are solved, and efficient carrier transport and stable photovoltaic cell performance are achieved.

CN119677378APending Publication Date: 2025-03-21ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411892706.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The thickness of the perovskite film in existing all-inorganic perovskite solar cells is relatively thin, which leads to difficulty in uniform formation and full coverage of the film. At the same time, the electric field driving force is weak and the carrier transport loss leads to low power conversion efficiency.

Method used

A thick film preparation method with a built-in electric field in gradient is adopted. By spin-coating CsPbIBr2 solution on a substrate with ZnO layer and spin-coating CsPbX3 solution on its surface, the built-in electric field is constructed through the concentration gradient and self-doping effect of halogen components to improve carrier mobility.

Benefits of technology

The optimal photovoltaic cell efficiency of 18.98% at a thickness of 3μm was achieved and excellent stability was shown, providing a feasible strategy for industrialized large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677378A_ABST
    Figure CN119677378A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a thick film with a gradient built-in electric field, and relates to the technical field of perovskite batteries, multi-Br component CsPbIBr2 microcrystal particles are adopted as a bottom layer to reduce a CsPbX3 nucleation potential barrier with few Br components on a top layer, and serve as a growth center of perovskite to accelerate the growth speed of a CsPbX3 film and promote CsPbX3 to grow along a preferred crystal face, so that the performance of the thick film with the gradient built-in electric field is improved, and the performance of the thick film with the gradient built-in electric field is improved. And the carrier mobility is improved. In the liquid film curing process, halogen components are mutually diffused by utilizing the concentration gradient difference of upper and lower I and Br components, and meanwhile, by utilizing the self-doping effect caused by the halogen element difference, the energy level arrangement is improved, a top partial p type semiconductor structure and a bottom partial n type semiconductor structure are successfully formed, a built-in electric field is constructed, and the separation and transmission driving force of charge carriers is increased. The built slowly-changed heterojunction effectively avoids the loss which is not beneficial to the performance of a battery device, such as sensitivity to external voltage change, carrier recombination loss at a PN junction interface and the like, caused by a traditional mutant heterojunction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite cells, and in particular to a preparation method and application of a thick film with a gradient built-in electric field. Background Art

[0002] Solar energy is abundant, clean, and environmentally friendly, and is a sustainable energy source. It is considered to be one of the main new energy sources to replace fossil fuels in the future. In recent years, emerging perovskite solar cells have received increasing attention due to their low cost, high PCE, and easy large-scale preparation. They are an important direction for the development of the photovoltaic industry in the future. Compared with organic-inorganic hybrid perovskite materials, all-inorganic perovskite solar cells (PAI-PSC) have better photothermal stability. Moreover, all-inorganic perovskites can achieve a wide range of adjustable band gaps (1.7-2.3 eV) by changing the I and Br content, thereby providing flexibility for the optical regulation of PSCs and having obvious advantages in the stacking or semi-transparent direction.

[0003] However, the perovskite film used in existing all-inorganic perovskite solar cells is relatively thin, which is not conducive to the uniform formation and full coverage of the film in large-scale coatings. In addition, the existing all-inorganic perovskite solar cells have a distinct heterojunction interface, resulting in a weak driving force in the formed PAI-PSCs electric field and low power conversion efficiency due to carrier transport losses. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a thick film with a gradient built-in electric field and its application.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0006] A method for preparing a thick film with a gradient built-in electric field is provided, comprising the following steps:

[0007] S1: dissolving CsI and PbBr2 in a dimethyl sulfoxide solution, cooling and filtering using a PTFE membrane to obtain a CsPbIBr2 solution;

[0008] S2: Spin-coating a CsPbIBr2 solution on a substrate with a ZnO layer and annealing to obtain a CsPbIBr2 seed layer;

[0009] S3: dissolving CsI, PbI2 and PbBr2 in a mixed solution of dimethyl sulfoxide and dimethylformamide; after cooling, filtering using a PTFE membrane to obtain a CsPbX3 solution;

[0010] S4: Spin-coat the CsPbX3 solution on the surface of the CsPbIBr2 seed layer, and anneal to obtain a thick film with a gradient built-in electric field.

[0011] Furthermore, step S1 is specifically as follows: dissolving CsI and PbBr2 in a mass ratio of 150-160:215-225 in a 0.6M dimethyl sulfoxide solution at 60°C, and the dosage ratio of CsI to dimethyl sulfoxide solution is 150-160 mg:1 mL.

[0012] Further, step S2 is specifically as follows: spin coating the CsPbIBr2 solution on the ZnO layer at a speed of 2000 rpm / s for 40 seconds; after the spin coating is completed, annealing is performed at 150°C for 5 minutes in a nitrogen atmosphere; the ratio of the amount of the CsPbIBr2 solution to the area of ​​the ITO / ZnO conductive glass substrate is 40 μL: 256 mm 2 .

[0013] Furthermore, step S3 is specifically as follows: CsI, PbI2 and PbBr2 with a mass ratio of 310-320:425-430:95-100 are dissolved in a mixed solution of dimethyl sulfoxide and dimethylformamide with a concentration of 1.1M at 60°C, wherein the molar ratio of dimethyl sulfoxide to dimethylformamide in the mixed solution is 7:4; and the dosage ratio of CsI to the mixed solution is 310-320 mg:1.1 mL.

[0014] Further, step S4 is specifically as follows: spin coating the CsPbX3 solution on the surface of the CsPbIBr2 seed layer at a speed of 500 rpm / s for 5 seconds, and then spin coating at a speed of 2500 rpm / s for 40 seconds; after the spin coating is completed, annealing is performed at 55°C for 1 minute in a nitrogen atmosphere and then at 300°C for 10 minutes; the ratio of the amount of the CsPbX3 solution to the area of ​​the CsPbIBr2 seed layer is 40 μL: 256 mm 2 .

[0015] The present invention also provides a thick film with a gradient built-in electric field prepared by the above preparation method.

[0016] The present invention also provides an application of the above-mentioned thick film in preparing a pure phase all-inorganic perovskite battery. The preparation method of the pure phase all-inorganic perovskite battery comprises the following specific steps:

[0017] A1: Prepare a ZnO electron transport layer on a cleaned ITO transparent conductive glass substrate;

[0018] A2: Prepare a thick film with a gradient built-in electric field on the surface of the ZnO electron transport layer;

[0019] A3: Preparation of Spiro-OMeTAD hole transport layer on the thick film surface;

[0020] A4: Use vacuum evaporation to deposit a layer of gold on the Spiro-OMeTAD hole transport layer as an electrode.

[0021] Furthermore, the specific steps of step A1 are:

[0022] A11: Use absorbent cotton dipped in detergent water to wipe the surface of the ITO transparent conductive glass substrate and then rinse with clean water;

[0023] A12: The rinsed substrate was ultrasonically cleaned with detergent water and pure water for 30 min in turn to remove organic matter on the surface;

[0024] A13: The substrate from which the organic matter on the surface has been washed away is then ultrasonically cleaned with acetone for 30 minutes, with anhydrous ethanol for 20 minutes, and with isopropanol for 20 minutes to wash away the impurities that are insoluble in water;

[0025] A14: Blow dry the washed ITO transparent conductive glass substrate with N2;

[0026] A15: Zn(CH3COO)2·2H2O and ethanolamine are mixed with dimethyl glycol to obtain a ZnO precursor; the dosage ratio of Zn(CH3COO)2·2H2O to dimethyl glycol is 100 mg:973 μL, and the volume ratio of ethanolamine to dimethyl glycol is 28.29:973 μL;

[0027] A16: filtering the ZnO precursor using a polyethersulfone filter with a filter diameter of 0.22 μm to obtain a ZnO precursor filtrate;

[0028] A17: Treat the ITO transparent conductive glass substrate obtained in step A14 with UV ozone for 20 minutes, spin-coat the ZnO precursor filtrate at a rotation speed of 4000 rpm / s for 30 seconds, and anneal at 200°C for 30 minutes to obtain a ZnO electron transport layer.

[0029] Furthermore, the specific steps of step A3 are:

[0030] B1: Dissolve Spiro-OMeTAD in chlorobenzene and let stand for 1-2 hours to obtain a mixed solution; the dosage ratio of Spiro-OMeTAD to chlorobenzene is 72.3 mg: 1 mL;

[0031] B2: Add tributyl phosphate, lithium salt solution and cobalt salt solution to the mixed solution obtained in B1, let it stand for 2-3 hours, and then filter it with a PTFE filter head with a filter diameter of 0.22 μm to obtain a Spiro-OMeTAD solution;

[0032] The volume ratio of tributyl phosphate, lithium salt and cobalt salt is 28.8:17.5:28.9; and the dosage ratio of tributyl phosphate to chlorobenzene is 28.8:1000;

[0033] The lithium salt solution is prepared by dissolving lithium bis(trifluoromethylsulfonyl)imide in acetonitrile, and the usage ratio of lithium bis(trifluoromethylsulfonyl)imide to acetonitrile is 520 mg: 1 mL;

[0034] The cobalt salt solution is prepared by dissolving Co(III)-TFSI salt in acetonitrile, and the usage ratio of Co(III)-TFSI salt to acetonitrile is 300 mg: 1 mL;

[0035] B3: Add the Spiro-OMeTAD solution dropwise onto the surface of the thick film and spin coat at 5000 rpm for 30 seconds to obtain the Spiro-OMeTAD hole transport layer.

[0036] Furthermore, in step A4, the electrode layer may be an Au electrode layer, or a MoO3 / Au / MoO3 transparent electrode layer;

[0037] When the electrode layer is an Au electrode layer, the evaporation parameters are: After 20 nm of deposition was deposited at a deposition rate of Evaporation to 50nm, and finally The rate of evaporation is up to 70nm;

[0038] When the electrode layer is a MoO3 / Au / MoO3 transparent electrode layer, the evaporation parameters are: 20nm bottom MoO3 was deposited at a rate of A gold electrode with a thickness of 12 nm was deposited at a rate of A 50nm top layer of MoO3 was evaporated at a rate of .

[0039] The beneficial effects of the present invention are:

[0040] The present invention adopts CsPbIBr2 microcrystalline particles with more Br components as the bottom layer, which can reduce the nucleation barrier of CsPbX3 with less Br components in the top layer, and accelerate the growth rate of CsPbX3 film as the growth center of perovskite, while promoting the growth of CsPbX3 along the preferred crystal plane, thereby improving the carrier mobility.

[0041] During the solidification process of the liquid film, the concentration gradient difference of the upper and lower I and Br components is used to diffuse the halogen components. At the same time, the self-doping effect caused by the difference in halogen elements is used to improve the energy level arrangement, successfully forming a semiconductor structure with a top biased to p-type and a bottom biased to n-type, constructing a built-in electric field, and increasing the separation and transmission driving force of charge carriers. The constructed slow-changing heterojunction effectively avoids the sensitivity to the change of the applied voltage brought by the traditional sudden heterojunction, the loss of carrier recombination at the PN junction interface, and other losses that are not conducive to the performance of the battery device.

[0042] An optimal PCE of 18.98% was achieved at a thickness of 3 μm and exhibited excellent stability, providing a feasible strategy for industrial large-area production. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Schematic diagram of the structure of the slow heterojunction constructed by secondary deposition of CsPbIBr2 seed layer and CsPbX3 layer;

[0044] Figure 2 The SEM images and grain statistics of the Pristine film and the Target film in Example 1;

[0045] Figure 3 The cross-sectional view and energy spectrum test diagram of the Pristine film and the Target film in Example 1;

[0046] Figure 4 The UV photoelectron spectrum and UV-visible molecular absorption spectrum of the Pristine film and the Target film in Example 1;

[0047] Figure 5 Schematic diagram of the energy band structure of the Pristine film and the Target film in Example 1;

[0048] Figure 6 The intensity modulation photocurrent spectrum comparison diagram, intensity modulation photovoltage spectrum comparison diagram and light injection linear boost comparison diagram of the control group and the experimental group in Example 2;

[0049] Figure 7 This is a graph showing the Newport test results for the control group and the experimental group in Example 2. DETAILED DESCRIPTION

[0050] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0051] Example 1

[0052] The steps include:

[0053] S1: Weigh 155.88 mg of CsI and 220.2 mg of PbBr2 and dissolve them in 1000 μL of 0.6 M dimethyl sulfoxide solution at 60°C. After cooling, filter the solution using a PTFE membrane with a filter diameter of 0.22 μm to obtain a CsPbIBr2 solution.

[0054] S2: Spin coating the CsPbIBr2 solution on a substrate with a ZnO layer of 16 mm*16 mm in size. In specific implementation, the substrate may be an ITO glass substrate, a glass slide or a silicon wafer. In this embodiment, the substrate is an ITO glass substrate. The specific operation of spin coating is as follows: after dropping 40 μL of the CsPbIBr2 solution on the surface of the ITO / ZnO conductive glass substrate, spin coating the ITO / ZnO conductive glass substrate at a speed of 2000 rpm / s for 40 seconds. In specific implementation, the ITO / ZnO conductive glass substrate is treated in a UV ozone cleaning machine for 5 minutes before spin coating the CsPbIBr2 solution.

[0055] After the spin coating is completed, annealing is performed at 150° C. for 5 min in a nitrogen atmosphere to obtain a CsPbIBr2 seed layer.

[0056] S3: 311.77 mg of CsI, 428.74 mg of PbI2 and 99.09 mg of PbBr2 were weighed and dissolved in a mixed solution of dimethyl sulfoxide and dimethylformamide at 60°C, wherein the mixed solution was obtained by mixing 700 μL of a 1.1 M dimethyl sulfoxide solution and 400 μL of a 1.1 M dimethylformamide solution; after cooling, the solution was filtered using a PTFE membrane with a filter diameter of 0.22 μm to obtain a CsPbX3 solution;

[0057] S4: Spin coating the CsPbX3 solution on the surface of the CsPbIBr2 seed layer. The specific operation of spin coating is as follows: after dropping 40 μL of CsPbX3 solution on the surface of the CsPbIBr2 seed layer, spin coating at a speed of 500 rpm / s for 5 seconds and then continue to spin coating at a speed of 2500 rpm / s for 40 seconds.

[0058] After the spin coating is completed, annealing is performed at 55°C for 1 min in a nitrogen atmosphere and then at 300°C for 10 min; a thick film with a gradient built-in electric field is obtained.

[0059] The principle of depositing an I-rich CsPbX3 layer on a Br-rich CsPbIBr2 seed layer is as follows: Figure 1As shown. By utilizing the difference in the concentration distribution of I and Br components, the CsPbX3 and CsPbIBr2 components diffuse into each other during the solidification process of the liquid film and construct a slowly deforming heterojunction, realizing the rearrangement of the film components and the secondary reconstruction of the crystal structure. Different from the traditional gradient homojunction, the self-doping effect caused by the differential distribution of halogen elements is utilized to successfully construct the distribution of the top p-type region and the bottom n-type region in the bulk phase of the perovskite film, construct a built-in electric field, and realize the slowly changing arrangement of energy levels and the highly directional transport of carriers.

[0060] A control group was set up. The control group was directly spin-coated on an ITO / ZnO conductive glass substrate to prepare a CsPbX3 thin film. A scanning electron microscope (German ZEISs Sigma 300) was used to detect the CsPbX3 thin film (Pristine) and the thick film with a gradient built-in electric field (Target). The results are shown in the figure. Figure 2 As shown, Figure 2 (a) is the SEM image of the pristine film. Figure 2 (c) is the grain statistics diagram of the pristine film; Figure 2 (b) is the SEM image of the Target film. Figure 2 (d) is the grain statistics of the Target film; Figure 2 It can be seen that the perovskite film prepared by the preparation method provided by the present invention has a larger grain size and a more uniform film surface.

[0061] The cross sections of the pristine membrane and the target membrane were photographed using a scanning electron microscope (ZEISs Sigma 300, Germany), and EDS analysis was performed on the pristine membrane and the target membrane using an energy dispersive spectrometer (Oxford Xplore 30, UK). The results are shown in Figure 2. Figure 3 As shown, Figure 3 (a) is the cross-sectional view of the pristine membrane. Figure 3 (b) is the I and Br element distribution diagram of the pristine film. Figure 3 (c) is the ratio diagram of I and Br elements at different positions of the pristine film. Figure 3 (d) is the cross-sectional view of the Target film. Figure 3 (e) is the I and Br element distribution diagram of the Target film. Figure 3 (f) is the ratio diagram of I and Br elements at different positions of the Target film.

[0062] Figure 3 (a) and Figure 3 The left side of (d) is the bottom of the corresponding film, and the right side is the top of the corresponding film;

[0063] Depend on Figure 3It can be seen that the halogen elements in the pristine film are distributed nonlinearly. At positions 1 to 3 of the film (from the bottom to the top), the element ratio of I to Br first increases and then decreases, such as Figure 3 (b) and 3(c). In contrast, the Target film shows a film thickness of 3 μm, indicating that the film prepared based on Fick diffusion engineering has a micron-level thickness, such as Figure 3 (d) As shown. The EDS reaction of the film prepared by the present invention shows that the I and Br elements present different distribution states. The I element is more concentrated on the upper surface and less distributed on the lower surface. In contrast, the Br component is generally not much different, as shown in FIG. Figure 3 (e) At the same time, from the bottom to the top (positions 1 to 3), the ratio of I to Br elements is positively correlated and gradually increases, as shown in Figure 3 (f) This result further proves the spontaneous diffusion of halogen components and the secondary reconstruction of the lattice structure.

[0064] The Pristine film and the Target film were tested by UV photoelectron spectroscopy and UV-visible molecular absorption spectroscopy using a UPS UV photoelectron spectrometer (Thermo escalab 250XI, USA). The results are as follows: Figure 4 As shown, Figure 4 a The left side is the UV photoelectron spectrum of the front side of the pristine film. Figure 4 a The right side shows the UV-visible molecular absorption spectrum of the front side of the pristine film; Figure 4 b The left side is the UV photoelectron spectrum of the front side of the Target film. Figure 4 b The right side shows the UV-visible molecular absorption spectrum of the front side of the Target film; Figure 4 c The left side is the UV photoelectron spectrum of the reverse side of the pristine film. Figure 4 c The right side is the UV-visible molecular absorption spectrum of the reverse side of the pristine film; Figure 4 a The left side is the UV photoelectron spectrum of the reverse side of the Target film. Figure 4 a The right side is the UV-visible molecular absorption spectrum of the reverse side of the Target film.

[0065] Depend on Figure 4 It can be seen that a semiconductor structure that is more p-type is formed on the top (front) of the Target film, while a semiconductor structure that is more n-type is formed on the bottom (reverse).

[0066] The band structures of the Pristine film and the Target film were detected using a UPS ultraviolet photoelectron spectrometer (Thermo escalab 250XI, USA). The results are as follows: Figure 5 As shown, Figure 5(a) is a schematic diagram of the energy band structure of the Target film; Figure 5 It can be seen that the Pristine film is an n-type semiconductor structure, while the Target film has successfully constructed p-type and n-type regions in the bulk phase, achieving a differential distribution of energy levels. The experimental group with a built-in electric field has a qV bi Increasing from 0.95 eV to 1.1 eV increases the built-in driving force, helps the drift of carriers, and further reduces the charge recombination at the interface, resulting in a larger electric field strength ε.

[0067] Example 2

[0068] The Target film prepared in Example 1 is used to prepare a perovskite cell, and the specific steps are as follows:

[0069] A1: Prepare a ZnO electron transport layer on a cleaned ITO transparent conductive glass substrate; the specific steps are:

[0070] A11: Use absorbent cotton dipped in detergent water to wipe the surface of the ITO transparent conductive glass substrate and then rinse with clean water;

[0071] A12: The rinsed substrate was ultrasonically cleaned with detergent water and pure water for 30 min in turn to remove organic matter on the surface;

[0072] A13: The substrate from which the organic matter on the surface has been washed away is then ultrasonically cleaned with acetone for 30 minutes, with anhydrous ethanol for 20 minutes, and with isopropanol for 20 minutes to wash away the impurities that are insoluble in water;

[0073] A14: Blow dry the washed ITO transparent conductive glass substrate with N2;

[0074] A15: Weigh 100 mg of Zn(CH3COO)2·2H2O and mix with 28.29 μL of ethanolamine in 973 μL of dimethylethylene glycol to obtain a ZnO precursor;

[0075] A16: filtering the ZnO precursor using a polyethersulfone filter with a filter diameter of 0.22 μm to obtain a ZnO precursor filtrate;

[0076] A17: Treat the ITO transparent conductive glass substrate obtained in step A14 with UV ozone for 20 minutes, spin-coat the ZnO precursor filtrate at a rotation speed of 4000 rpm / s for 30 seconds, and anneal at 200°C for 30 minutes to obtain a ZnO electron transport layer.

[0077] A2: A Target film having a gradient built-in electric field is prepared on the surface of the ZnO electron transport layer by the method in Example 1;

[0078] A3: Prepare a Spiro-OMeTAD hole transport layer on the surface of the Target membrane; the specific steps are: weigh 72.3 mg of Spiro-OMeTAD, dissolve it in 1 mL of chlorobenzene solution, shake until dissolved, and let it stand for 1-2 hours, then add 28.8 μL of TBP, 17.5 μL of lithium salt and 28.9 μL of cobalt salt, let it stand for 2 to 3 hours, and filter with a 0.22 μm PTFE filter head to obtain the Spiro-OMeTAD solution for use.

[0079] Take 40 μL of Spiro-OMeTAD solution and evenly drop it on the Target film. After rotating at 5000 rpm for 30 seconds, the Spiro-OMeTAD hole transport layer is obtained.

[0080] A4: Use vacuum evaporation to deposit a layer of gold on the Spiro-OMeTAD hole transport layer as an electrode.

[0081] A control group (Pristine) was set up. The difference between the control group and the above experimental group (Target) was that in step A2, a Pristine film was prepared on the surface of the ZnO electron transport layer using the method in Example 1.

[0082] The PAIOS multifunctional carrier characteristic analysis system (PAIOS of Fluxim-20118) was used to perform intensity modulation photocurrent spectrum detection, intensity modulation photovoltage spectrum detection and light injection linear boost detection on the control group and the experimental group. The test results are shown in the figure. Figure 6 As shown, Figure 6 (a) is a comparison diagram of intensity modulated photocurrent spectra; Figure 6 (b) is a comparison diagram of intensity modulated photovoltage spectra; Figure 6 (c) is a comparison diagram of linear boost of light injection; Figure 6 (a) and Figure 6 (b) It can be seen that, sc From 215.9ns to 53.1ns, L D From 354nm to 692nm, Figure 6 (c) It can be seen that compared with the control group, the photoinduced charge carrier extraction showed that the carrier mobility of the experimental group increased from 1.24×10 -4 cm 2 / Vs increased to 2.68×10 -4 cm 2 / Vs, proving that the experimental group can significantly improve the carrier mobility.

[0083] A Newport test system (Enlitech SS-X180R, USA) was used to draw JV curves for the control group and the experimental group, to detect the external quantum efficiency and to count the box lines of the two groups. Before each test, a standard solar simulator (NewportOriel 94043A, AM 1.5G 100mW / cm 2 ) and standard silicon cells for light intensity calibration; the results are shown in Figure 7 As shown, Figure 7 (a) is a comparison diagram of JV curves; Figure 7 (b) is a comparison chart of external quantum efficiency; Figure 7 (c) is a box-line statistical comparison chart. Figure 7 It can be seen that the perovskite battery made using the Target film prepared by the present invention has better stability and better power conversion efficiency.

Claims

1. A method for preparing a thick film with a gradient built-in electric field, characterized in that: The steps include: S1: dissolving CsI and PbBr2 in a dimethyl sulfoxide solution, cooling and filtering using a PTFE membrane to obtain a CsPbIBr2 solution; S2: Spin-coating a CsPbIBr2 solution on a substrate with a ZnO layer and annealing to obtain a CsPbIBr2 seed layer; S3: dissolving CsI, PbI2 and PbBr2 in a mixed solution of dimethyl sulfoxide and dimethylformamide; after cooling, filtering using a PTFE membrane to obtain a CsPbX3 solution; S4: Spin-coating the CsPbX3 solution on the surface of the CsPbIBr2 seed layer, and annealing to obtain the thick film with the gradient built-in electric field.

2. The method for preparing a thick film with a gradient built-in electric field according to claim 1, characterized in that: The step S1 specifically comprises: dissolving CsI and PbBr2 in a mass ratio of 150-160:215-225 in a 0.6M dimethyl sulfoxide solution at 60°C, and the dosage ratio of CsI to dimethyl sulfoxide solution is 150-160 mg:1 mL.

3. The method for preparing a thick film with a gradient built-in electric field according to claim 1, characterized in that: The step S2 specifically includes: spin coating the CsPbIBr2 solution on the ZnO layer at a speed of 2000 rpm / s for 40 seconds; after the spin coating is completed, annealing is carried out at 150° C. for 5 minutes in a nitrogen atmosphere; the ratio of the amount of the CsPbIBr2 solution to the area of ​​the ITO / ZnO conductive glass substrate is 40 μL: 256 mm 2 .

4. The method for preparing a thick film with a gradient built-in electric field according to claim 1, characterized in that: The step S3 is specifically as follows: dissolving CsI, PbI2 and PbBr2 in a mass ratio of 310-320:425-430:95-100 in a mixed solution of dimethyl sulfoxide and dimethylformamide with a concentration of 1.1M at 60°C, wherein the molar ratio of dimethyl sulfoxide to dimethylformamide in the mixed solution is 7:4; and the dosage ratio of CsI to the mixed solution is 310-320 mg:1.1 mL.

5. The method for preparing a thick film with a gradient built-in electric field according to claim 1, characterized in that: The step S4 is specifically as follows: spin coating the CsPbX3 solution on the surface of the CsPbIBr2 seed layer at a speed of 500 rpm / s for 5 seconds, and then spin coating at a speed of 2500 rpm / s for 40 seconds; after the spin coating is completed, annealing is performed at 55°C for 1 minute in a nitrogen atmosphere and then at 300°C for 10 minutes; the ratio of the amount of the CsPbX3 solution to the area of ​​the CsPbIBr2 seed layer is 40 μL: 256 mm 2 .

6. A thick film with a gradient built-in electric field prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the thick film according to claim 6 in preparing a pure phase all-inorganic perovskite battery, characterized in that: The preparation method of the pure phase all-inorganic perovskite battery comprises the following specific steps: A1: Prepare a ZnO electron transport layer on a cleaned ITO transparent conductive glass substrate; A2: Prepare a thick film with a gradient built-in electric field on the surface of the ZnO electron transport layer; A3: Preparation of Spiro-OMeTAD hole transport layer on the thick film surface; A4: Use vacuum evaporation to deposit a layer of metal on the Spiro-OMeTAD hole transport layer as an electrode.

8. The use according to claim 7, characterized in that: The specific steps of step A1 are: A11: Use absorbent cotton dipped in detergent water to wipe the surface of the ITO transparent conductive glass substrate and then rinse with clean water; A12: The rinsed substrate was ultrasonically cleaned with detergent water and pure water for 30 min in turn to remove organic matter on the surface; A13: The substrate from which the organic matter on the surface has been washed away is then ultrasonically cleaned with acetone for 30 minutes, with anhydrous ethanol for 20 minutes, and with isopropanol for 20 minutes to wash away the impurities that are insoluble in water; A14: Blow dry the washed ITO transparent conductive glass substrate with N2; A15: Zn(CH3COO)2·2H2O and ethanolamine are mixed with dimethyl glycol to obtain a ZnO precursor; the dosage ratio of Zn(CH3COO)2·2H2O to dimethyl glycol is 100 mg:973 μL, and the volume ratio of ethanolamine to dimethyl glycol is 28.29:973 μL; A16: filtering the ZnO precursor using a polyethersulfone filter with a filter diameter of 0.22 μm to obtain a ZnO precursor filtrate; A17: Treat the ITO transparent conductive glass substrate obtained in step A14 with UV ozone for 20 minutes, spin-coat the ZnO precursor filtrate at a rotation speed of 4000 rpm / s for 30 seconds, and anneal at 200°C for 30 minutes to obtain a ZnO electron transport layer.

9. The use according to claim 7, characterized in that: The specific steps of step A3 are: B1: Dissolve Spiro-OMeTAD in chlorobenzene and let stand for 1-2 hours to obtain a mixed solution; the dosage ratio of Spiro-OMeTAD to chlorobenzene is 72.3 mg: 1 mL; B2: Add tributyl phosphate, lithium salt solution and cobalt salt solution to the mixed solution obtained in B1, let it stand for 2-3 hours, and then filter it with a PTFE filter head with a filter diameter of 0.22 μm to obtain a Spiro-OMeTAD solution; The volume ratio of tributyl phosphate, lithium salt and cobalt salt is 28.8:17.5:28.9; and the dosage ratio of tributyl phosphate to chlorobenzene is 28.8:1000; The lithium salt solution is prepared by dissolving lithium bis(trifluoromethylsulfonyl)imide in acetonitrile, and the dosage ratio of lithium bis(trifluoromethylsulfonyl)imide to acetonitrile is 520 mg: 1 mL; The cobalt salt solution is prepared by dissolving Co(III)-TFSI salt in acetonitrile, and the usage ratio of Co(III)-TFSI salt to acetonitrile is 300 mg: 1 mL; B3: Add the Spiro-OMeTAD solution dropwise onto the surface of the thick film and spin coat at 5000 rpm for 30 seconds to obtain the Spiro-OMeTAD hole transport layer.

10. The use according to claim 8, characterized in that: In the step A4, the electrode layer may be an Au electrode layer, or a MoO3 / Au / MoO3 transparent electrode layer; When the electrode layer is an Au electrode layer, the evaporation parameters are: After 20 nm of deposition was deposited at a deposition rate of Evaporation to 50nm, and finally The rate of evaporation is up to 70nm; When the electrode layer is a MoO3 / Au / MoO3 transparent electrode layer, the evaporation parameters are: 20nm bottom MoO3 was deposited at a rate of A gold electrode with a thickness of 12 nm was deposited at a rate of A 50nm top layer of MoO3 was evaporated at a rate of .